Patterns and functions of I in academic writing: From a local grammar approach. Issue 61 (January 2023) - Li, Jingjie; Ye, Ting
Abstract: This paper describes the co-selection of patterns and functions of the authorial I in soft science articles under the analytical framework of local grammar. Based on the taxonomy of Tang & John (1999), we generalized four functional categories in terms of the writer roles enacted by I : i.e. I as architect, I as data analyser, I as recounter of research process, and I as opinion holder/originator . We then identified the frequent semantic-functional patterns and lexico-grammatical patterns of I under each category of function. In so doing, we explored the connections among patterns and collocations of I and functions that I is used for. It is hoped that this paper would help novice soft science writers to gain a better understanding about how to use the authorial I more appropriately to construct authorial identity in academic writing.